RNA Interference Screen Identifies VEGFR1 as Potentially Synthetic Lethal to Aberrant Wnt/β-catenin Activation in Colon Cancer - Naik, Snehal (2009)
PURPOSE: The Wnt/β-catenin (β-cat) signaling cascade is a key regulator of development, and dysregulation of Wnt/β-cat contributes to selected cancers, such as colorectal, breast and hepatocellular carcinoma, through abnormal activation of Wnt target genes. To identify novel modulators of the Wnt/β-cat pathway which may emerge as therapeutic targets, we performed an unbiased high-throughput RNA interference screen. EXPERIMENTAL DESIGN: A synthetic oligonucleotide siRNA library targeting 691 known and predicted human kinases was screened in Wnt3a-stimulated human cells in a live cell luciferase assay for modulation of Wnt/β-cat-dependent transcription. Follow-up studies of a selected high-confidence “hit” were conducted. RESULTS: A robust quartile-based statistical analysis and secondary screen yielded several kinases worthy of further investigation, including Cdc2L1, Lmtk3, Pank2, ErbB3, and of note, vascular endothelial growth factor receptor-1 (VEGFR1/Flt1), a receptor tyrosine kinase with putative weak kinase activity conventionally believed to be a negative regulator of angiogenesis. A series of loss-of-function, genetic null, and VEGFR tyrosine kinase inhibitor assays further revealed that VEGFR1 is a positive regulator of Wnt signaling that functions in a glycogen synthase kinase-3β (GSK3β)-independent manner as a potential synthetic lethal target in Wnt/β-cat-addicted colon carcinoma cells. CONCLUSION: This unanticipated non-endothelial link between VEGFR1 tyrosine kinase activity and Wnt/β-cat signaling may refine our understanding of aberrant Wnt signaling in colon carcinoma and points to new combinatorial therapeutics targeted to the tumor cell compartment, rather than angiogenesis, in the context of colon cancer.